A force distribution measurement system for soft tissue balancing during total knee arthroplasty - Mohd Hanafi Mat Som (University of Fukui, 2015)
The ligament balance, which is a crucial parameter for the success of Total Knee Arthroplasty (TKA) only qualitatively assessed in a manner of subjective feel of the surgeon. Thus, the goal of this study is to develop a force distribution measurement system based on pressure-sensitive conductive rubber.